Dendrimers nanomedicine concept, theory and regulatory perspectives - Mehra, Narinder K. (Narinder Kumar), 1949-; Jain, Keerti (Boca Raton : CRC Press, 2021)
Dendrimers, hyperbranched macromolecules, emerged just few decades ago but show promising potential as drug delivery nanocarriers, theranostic agents and gene vectors; in the pharmaceutical research and innovation area as well as in other healthcare applications. Although tremendous advancements have been made in dendrimer chemistry and their applications since their emergence, the synthesis, development and design of pure and safe dendrimer-based products have been a major challenge in this area. This book, edited by well-known researchers in the area of nanomaterials and drug-based drug delivery applications, exhaustively covers the nanotechnological aspects, concepts, properties, characterisation, application, biofate and regulatory aspects of dendrimers. It includes sixteen vivid chapters by renowned formulators, researchers and academicians from all over the world, highlighting their specialised areas of interest in the fields of chemistry, biology, pharmacy and nanomedicine. Features: Highlights dendrimers' advancements in nanomedicine in the development of safe healthcare and biotechnological products Covers physicochemical aspects, biofate, drug delivery aspects and gene therapy using dendrimers Covers biomedical application of dendrimers in the field of biological sciences Gives examples of dendrimer-guest interaction chemistry Dendrimers in Nanomedicine: Concept, Theory and Regulatory Perspectives provides the comprehensive overview of the latest research efforts in designing, optimising, development and scale-up of dendrimer-mediated delivery systems. It analyses the key challenges of synthesis, design, molecular modelling, fundamental concepts, drug delivery aspects, analytical tools and biological fate as well as regulatory consideration to the practical use of dendrimer application. Dr. Neelesh Kumar Mehra Assistant Professor of Pharmaceutics in the Department of Pharmaceutics at the National Institute of Pharmaceutical Education & Research (NIPER), Hyderabad, India. He has authored more than sixty peer-reviewed publications in highly reputed international journals, as well as book chapters and contributions on two patents. Dr. Mehra has 11 years of rich research and teaching experience in the formulation and development of complex, innovative biopharmaceutical products including micro- and nanotechnologies for regulated markets. Dr. Keerti Jain Assistant Professor of Pharmaceutics in the Department of Pharmaceutics, NIPER, Raebareli, India. For more than 10 years, she has been actively engaged in formulation and development of nanomedicines. Dr. Jain has supervised masters and doctoral pharmaceutics students in their research works which have been published in high quality, good impact factor journals. She has also authored more than 60 international manuscripts in peer reviewed high impact journals. In 2019, she was awarded the prestigious ICMR-Amir Shakuntala Award.
OCLC-licensed vendor bibliographic record.
Keywords: Dendrimers; Nanoscience; SCIENCE / Biotechnology; MEDICAL / Pharmacology